Access denied: studying up in the criminological encounter - Oleson, James C. (Criminological encounters, 2018)
Criminology, like other social sciences, tends to focus on vulnerable populations. Criminologists know a great deal about the crimes of the poor, prisoners, and young people, but little about the offences of those possessing education, wealth, and power. This is unfortunate, as in terms of both financial and physical harm, the crimes of the powerful dwarf those committed by the vulnerable. Criminologists know so little about the crimes of the powerful, partly because research access is denied, and this disparate research access reproduces particular forms of knowledge within criminology. For example, although self-report survey items about petty offences reveal a negative relationship between IQ and prevalence rates 'a finding that is consistent with most IQ-crime research' survey items about white-collar offences reveal a positive relationship between IQ and prevalence. Yet because white-collar crimes are not typically included in self-report research, this relationship goes unreported. These correlates of petty and white-collar offences suggest that the self-report methodology, if employed with new populations, has the potential to reveal new features within the dark figure of crime.